Peran Kinerja Karyawan Pada Peningkatan Produktivitas Rumah Makan Padang Alam Minang - Lulu Kamelia; Melanda Wulandari; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Universitas 45 Surabaya, 2023)
This visit aims to equip students with various knowledge about the world of business and management. This industrial/umkm visit is carried out directly to the field, because it will provide real education for students to see the business potential that exists around them. The phenomenon of Padang Restaurants in Indonesia according to PERGIKULINER, Nasi Padang is rice that comes from Padang. In fact, Nasi Padang itself is Nasi Rames that comes from Padang because in their area of origin there are no Padang restaurants but ordinary rice restaurants. The method used is descriptive method. Data collection techniques, namely observational techniques, interviews and documentation, this is a data collection method that is carried out by direct observation by observing things that are done at the Alam Minang Restaurant. During this visit we explained the differences between Padang Alam Miang restaurants when they have employees and when they don't have employees, it can be seen that the role of employees is very helpful in increasing productivity at Padang Alam Minang restaurants. The conclusion of this visit is about the Alam Minang restaurant before having employees and changes after having employees, when before having employees the difficulties experienced by Mr. very helpful and important in increasing productivity at the Alam Minang restaurant.